Resilience: professional competence of the business administrator - Delgado Litardo, Boris; Flores Sánchez, José Alejandro; Segarra Jaime, Humberto Pedro; Meza Salvatierra, Johana Katiusca (Revista Universidad de Guayaquil, 2021)
At present, it has become more relevant to identify continuous evaluation mechanisms and business processes with the aim of absorbing impacts and giving an adequate response to change. The objective of this research is to carry out a documentary review of the term resilience, its origin, characteristics, benefits, and its application in the different social and organizational disciplines. Mention how the individual and collective behavior of the human being can affect business stability. Furthermore, to explaining how this ability is a key competence for business managers, through the implementation of transformative strategic thinking, creating a more communicative and committed work environment. Finally, the importance of carrying out complementary post-pandemic studies of crisis management and business continuity plans is evident.